Perancangan Sistem Pendukung Keputusan Pemilihan Supplier dengan Metode Analytical Hierarchy Process (AHP) Pada CV. Safina Abadi - Hidayat, Jatmiko Tejo; Diartono, Dwi Agus (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
The contractor industry, including CV Safina Abadi, has a significant need for selecting the right suppliers to ensure smooth project execution. Optimal supplier selection can affect various critical aspects of a construction project, such as product quality, availability, competitive pricing, service, and reputation. However, due to the numerous supplier options available, companies often face difficulties in evaluating and choosing the most suitable supplier based on their needs and criteria. Therefore, utilizing a Decision Support System (DSS) with the Analytical Hierarchy Process (AHP) method presents an effective solution to assist companies in the supplier selection process. By employing AHP, companies can model a hierarchy of selection criteria, from main criteria down to more detailed sub-criteria. AHP further enables companies to measure and compare the relative weights of each criterion and sub-criterion, providing recommendations for the most optimal supplier based on the company's preferences and requirements. This research aims to design and implement a Decision Support System using the AHP method to assist in supplier selection for CV Safina Abadi. It is hoped that this study will contribute to improving the efficiency and effectiveness of supplier selection, thereby enhancing overall project performance in the construction industry.